Reproduksi Ketimpangan Gender Dalam Proses Sosialisasi Keluarga Pada Usia Dewasa Awal - Tita Hidayat; Salsabila Syafiqah; Sri Damayanti (Jurnal Keluarga Sehat Sejahtera, 2026)
This Study aims to comprehensively examine how the process of gender socialization within the family works to reproduce and internalize gender inequalities in individuals in early adulthood. Using a descriptive qualitative approach, the study involved 12 informants selected through purposive sampling based on birth order and gender. Data were collected through semi-structured interviews and observation, then analyzed using the Miles and Huberman model. The results indicate that gender socialization occurs through advice, rules, and behavioral examples, with the mother serving as the most dominant agent of socialization. Significant disparities are evident in the heavier domestic workload borne by women and the more flexible social control and permissions granted to men, which are often normalized as acceptable. Although there is room for negotiation, most of these values remain internalized as part of one’s identity. In conclusion, socialization within the family consistently reproduces gender inequality by normalizing traditional roles as a habitus; therefore, efforts to deconstruct patriarchal culture within family education are necessary.